The autonomic (visceral motor) nervous system - Sukhomlinova, I. Ye.; Voteva, V. Ye.; Tichonovskay, M. A.; Chugin, S. V.; Yeryomina, A. K.; Pashko, O. Ye.; Сухомлінова, Ірина Євгенівна; Вотєва, Ванда Євгенівна; Тихоновська, Марина Анатоліївна; Чугін, Сергій Вячеславович; Єрьоміна, Алла Кузьмівна; Пашкова, Олена Єгорівна (Zaporizhzhia state medical university, 2017)
This manual is recommended for II year students of International Faculty of specialty "General medicine" studying biological chemistry, as additional material to prepare for practical training semantic modules 4 of module 1 and licensing exam "KROK 1: General medical training".
Автономна (вісцеральна моторна) нервова система